Corporate Social Responsibility and Government: The Role of Discretion for Engagement with Public Policy. Issue 2 (21st April 2022) - Knudsen, Jette Steen; Moon, Jeremy
Abstract : We investigate the relationship of corporate social responsibility (CSR) (often assumed to reflect corporate voluntarism) and government (often assumed to reflect coercion). We distinguish two broad perspectives on the CSR and government relationship: the dichotomous (i.e., government and CSR are / should be independent of one another) and the related (i.e., government and CSR are / should be interconnected). Using typologies of CSR public policy and of CSR and the law, we present an integrated framework for corporate discretion for engagement with public policy for CSR. We make four related contributions. First, we explain the dichotomous and the related perspectives with reference to their various assumptions and analyses. Second, we demonstrate that public policy for CSR and corporate discretion coexist and interact. Specifically, we show, third, that public policy for CSR can inform and stimulate corporate discretion and, fourth, that corporations have discretion for CSR, particularly as to how corporations engage with such policy.